Astrocytic-neuronal-astrocytic Pathway Selection for Formation and Degradation of Glutamate/GABA - Tiago B. Rodrigues (Frontiers Research Topics, 2014)
Endocrinological research early recognized the importance of intercellular interactions and realized the importance of glutamatergic and GABAergic signaling. In turn this signalling depends on elaborate interactions between astrocytes and neurons, without which neurons would be unable to produce, reuse and metabolize transmitter glutamate and GABA. Details of these subjects are described in this Research Topic by key investigators in this field. It focuses on the intricate and extremely swift pathway producing these amino acid transmitters from glucose in brain but also discusses difficulties in determining expression of some of the necessary genes in astrocytes and related processes in pancreatic islets. However, it does not discuss how closely associated astrocytes and neurons are anatomically, enabling these interactions. This is elegantly shown in this cover image, kindly provided by Professor Andreas Reichenbach (University of Leipzig, Germany).